El acoso moral laboral como generador de violación de Derechos Constitucionales de los trabajadores en el Ecuador - Carrasco Lara, Segundo Fausto (2015)
Imagine you for a brief moment today , like yesterday , and the day before yesterday , and many other days " you need to work ." Imagine that in his work today , like yesterday, and many other days , they will find an empty totally adverse environment , silence, isolation , employers , bosses with previously talked and now they ignore that at best , because there could be a more difficult scenario . laugh and scoff you , who try to attack him : you insult him, you despise the little work they send you , or lie about the results achieved , or worse , will be charged with robbery, theft , etc. This imaginary location or others . like, the many people live every day in our country. it is one of the main problems being played in many countries where better employment benefits for its workers are sought, in an effort to force them to give ills. This social phenomenon is not working other than a tendentious and malicious work pressure that affects the physical, psychological and social well-being of the victim, and that is unacceptable for the workplace. Workplace bullying in the Constitution of the Republic and other laws not stated explicitly but implied, because it provides the right to a dignified, fair, favorable environment , etc. . The Constitution of Montecristi to regulate social and cultural rights set out in Article 35, that work is a right and a social duty enjoying state protection . This article seeks to ensure and guarantee workers the respect for their dignity and a decent life through a dignified and stable work activity , which is not met, and that when applying the labor recurring harassment and the indifference of society, what is done is institutionalize practice reprehensible and objectionable from every point of view as the labor bullying seeks nothing more than dismiss the worker voluntarily through constant harassment and harassment by their employers , so that terms such as dignity and stability become a utopia. This research work addresses this problem from various aspects and approaches to understanding the complexity of workplace harassment also known as labor bullying . And he made sustained in recent research data , publications and surveys , and from the extensive literature of the authors about bullying , both in his expert appearance , psychological, and preventive , and legal . This research is the result of an academic effort tesista subscribed , supported by the general guidelines of the National University of Loja, and their teachers